PENGEMBANGAN DAN PEMBERDAYAAN INTEGRITAS PENDIDIKAN MASYARAKAT KELURAHAN JURUMUDI MELALUI PENGEMBANGAN POJOK BACA DAN PROGRAM EDUKASI MASYARAKAT - Utami, Amaira; Kristiawan, Nana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2025)
Education plays an important role in human life as a vehicle for creating high-quality human resources capable of competing globally. Survey data in Kampung Bulak Kambing, Tangerang City, shows that only about 2% of the community continues their higher education to the Diploma (D1) or undergraduate (S1) level. Therefore, the community service carried out for three months from January to March 2024 in Kampung Bulak Kambing, Jurumudi Village aimed at developing and empowering educational integrity of community. The three stages of community service involve the preparation, implementation and evaluation stages. There are five main programs conducted in this community service program, namely (1) tutoring education program; (2) religious education assistance; (3) storytelling assistance; (4) healthy gymnastics and educational games; (5) establishment of a reading corner. The results of community service show that community participation and motivation in implementing education programs have increased. In addition, it is evident that the community's knowledge, literacy, and intellectual abilities have increased after participating in the education integrity development and empowerment program based on evaluation results.